Handbook of geometric topology - Daverman, Robert J.; Sher, R. B.; ScienceDirect eBooks (Amsterdam ; New York : Elsevier, 2002)
Geometric Topology is a foundational component of modern mathematics, involving the study of spacial properties and invariants of familiar objects such as manifolds and complexes. This volume, which is intended both as an introduction to the subject and as a wide ranging resouce for those already grounded in it, consists of 21 expository surveys written by leading experts and covering active areas of current research. They provide the reader with an up-to-date overview of this flourishing branch of mathematics.
Topics in transformation groups / A. Adem and J.F Davis -- R-trees in topology, geometry, and group theory / M. Bestvina -- Geometric structures on 3-manifolds / E Bonahon -- Dehn surgery on knots / S. Boyer -- Piecewise linear topology / J.L. Bryant -- Geometric group theory / J.W. Cannon -- Infinite dimensional topology and shape theory / A. Chigogidze -- Nonpositive curvature and reflection groups / M.W Davis -- Cohomological dimension theory / J. Dydak -- Flows with knotted closed orbits / J. Franks and M.C. Sullivan -- Nielsen fixed point theory / R. Geoghegan -- Mapping class groups / N.V. Ivanov -- Seifert manifolds / K.B. Lee and E Raymond -- Quantum invariants of 3-manifolds / W.B.R. Lickorish -- L2-invariants of regular coverings of compact manifolds and CW-complexes / W. Lack -- Metric spaces of curvature> k / C. Plaut -- Hyperbolic manifolds / J.G. Ratcliffe -- Heegaard splittings of compact 3-manifolds / M. Scharlemann -- Representations of 3-manifold groups / P.B. Shalen -- Topological rigidity theorems / C.W. Stark -- Homology manifolds / S. Weinberger.
Includes bibliographical references and indexes.
Print version record.
Elsevier
Keywords: Topology; Topologie; MATHEMATICS -- Topology; Topology; Electronic books